Studi Evaluasi Sistem Drainase Di Kawasan Komplek Harapan Indah Kota Sorong Dengan Menggunakan Software EPA-SWMM 5.1 - Ar-Rafi, Muhammad Husein; Pamudjianto, Agung (LRI Universitas Muhammadiyah Sorong, 2023)
Sorong City is a developing city, which in recent years has been intensively developing facilities and infrastructure in all fields. Some of the developments that are intensively carried out are road construction and housing settlement development. Sorong City, especially the Harapan Indah Complex area, is one of the developing areas that is prone to flooding and local inundation during the rainy season. The purpose of this study is to determine the condition of the drainage system in Harapan Indah in accommodating the maximum rain discharge for a certain period of time. The research method used is to process data obtained from the field and then process it using EPA-SWMM software to simulate drainage flow due to surface runoff that occurs. From the results of simulations using EPA-SWMM software, the condition of the drainage system in the Harapan Indah complex area is still often overflowing, obtained from the results of the analysis of regional channels on Jalan Cendrawasih most overflowing in the return period of 2 years, 5 years & 10 years. On Jalan Cendrawasih there are overflowing channels, namely 18 channels with a 2-year return period calculation, 24 channels with a 5-year return period calculation and 25 channels with a 10-year return period calculation.